الإشهاد على الطلاق والرجعة - دراسة فقهية مقارنة - عيشاوي, زينب (University of Eloued-جامعة الوادي, 2016)
This message Taatnolt important issue of the issues relating to family life, a certification of divorce and Alrdjah- doctrinal comparative study - which touched on two chapters, the first chapter includes the concept of certification and divorce, and divided into three sections, Valambges first talking about the concept of certification for being a key topic, the topic the second includes the concept of divorce, and the third section included the rule of certification of the divorce and its effects, while in the second chapter touched on the talk about taking back the rule of certification on it and contained this chapter as well as the two sections the former included the concept of irreversibility (definition, rule, conditions) and the second included the rule of certification of the irreversibility and their implications, and concluded the letter the results reached by the subject, and some of the recommendations may be that Tnfna and served on the Muslims' houses.
مذكرة ماستر
Keywords: الاشهاد على الطلاق والرجعة/دراسة فقهية مقارنة; Witnessing divorce and return / comparative jurisprudence study